ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA PEMERINTAH DAERAH DI KABUPATEN KARANGANYAR - Pradina, Mirna; Sarwono, Aris Eddy; Saptantinah P.A, Dewi (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
This research was conducted on 41 Regional Apparatus Organizations inKaranganyar Regency, the type of data used is quantitative data. The data sourceused is primary data. The entire population in this study were all Civil Servants inthe Karanganyar Regency. The sample used in this study was employees offinance in each Regional Apparatus Organization in Karanganyar Regency. Thesampling technique is done by using purposive sampling method. This studyshows that the Financial Accounting System, financial management, andaccountability have significant impact on the performance of local governments.The moderation regression test results in this study indicate that internalsupervision has the effect of strengthening financial management andaccountability variables on local government performance as a moderatingvariable